Modelling glacial abrupt climate changes and their impact on the Northern Hemisphere glacial ice sheets - Banderas Carreño, Rubén (Universidad Complutense de Madrid, 2019)
During the last glacial period (LGP), the North Atlantic region experienced aseries of abrupt climate changes known as Dansgaard-Oeschger (D/O) eventswhich comprised rapid temperature excursions from cold to relatively mild climaticconditions and widespread impacts recurring on millennial time scales. Theprevailing paradigm to explain these glacial abrupt climate changes involves reorganisationsof the Atlantic meridional overturning circulation (AMOC). Coldclimatic conditions in the North Atlantic are thought to be associated to a weakAMOC regime in which the heat transport towards the North Atlantic is stronglydiminished, while relatively warm climatic conditions are thought to result froma reinvigoration of this northward heat transport. Freshwater uxes have beencommonly invoked to be responsible for perturbing the AMOC stability, thuspromoting these abrupt climate changes. However, there is still a high degreeof uncertainty regarding the origin and magnitude of these freshwater uxes, afactor that challenges the implication of this forcing in glacial abrupt climatechanges.